Reporting behavior and transparency in European banks' country-by-country reports - Verena K. Dutt; Katharina Nicolay; Christoph Spengel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The public CbCR requirement for EU financial institutions leaves leeway to the reporting firms as regards the calculating and presentation of the data. Based on a sample of CbCRs published by EU-headquartered multinational bank groups, we analyze the reporting behavior and the degree of transparency across the reports. We observe a large heterogeneity with respect to the place of publication of the CbCR, its content, the readability of the data tables as well as the list of entities that should be published together with the by-country data. We also identify differences between headquarter countries, with CbCRs prepared by bank groups from the United Kingdom and Germany being the most transparent. Inconsistencies in reporting inhibit the interpretability and the comparability of the data. We conclude that the specification of the underlying data source and of the applicable consolidation scope as well the establishment of uniform definitions of the reportable items are essential for an appropriate consideration of the reports by all addressees. Our analyses are particularly important in light of the proposal for a public CbCR for large multinational firms in the EU.
Keywords: H25; H26; G21; G28; 330; Country-by-Country Reporting; Financial Institutions; Public Disclosure; Reporting Behavior; Tax Transparency